Is hypoxic/altitude training an important topic in the field of hypoxia? - Millet, G. P.; Burtscher, M.; Burtscher, J. (Journal of Science in Sport and Exercise, 2022)
Hypoxia is an essential topic in medical or biological sciences. The main aims of the present study were to examine the most important medical articles (i.e., the top 100 most cited) on hypoxia. We examine how the Nobel-prize awarded hypoxia inducible factor (HIF)-pathway discovery in the early 1990s has changed the thematic composition of this body of literature, with a special emphasis on the studies linking hypoxia and cancer. We searched Pubmed for articles with the terms #Hypox, #Altitude, or #Mountain in the title that have been published in biomedical journals and ranked the articles on their number of citations in Web of Science. A second search was performed in all journals for articles related to hypoxia and cancer. Strikingly, only 12 of the top-100 most-cited articles on hypoxia and only 3 articles of the top-100 articles related to cancer were published before 1995. Moreover, only 5 articles from prior 1995 reached 1000 citations, while 27 articles published in 1995 or later were cited more than 1000 times, most of them on the HIF-1 pathway. Eighty percent of the top-100 articles were related to the HIF pathway, while there were no articles on the application of hypoxia either for therapeutic use (i.e., hypoxic conditioning in patients) or for performance enhancement (i.e., altitude training in athletes). In conclusion, the early-1990s discovery of the HIF pathway and of its molecular regulation has shifted the focus of hypoxia research towards molecular mechanisms and consequences of tissue hypoxia, most notably in cancer. The importance of studies focusing on clinical and performance applications of systemic hypoxia is relatively lower.